The Impact of the Internet on Relational Goods: Empirical Evidence from European Countries - Keziban Altun Erdoğdu (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Along with behavioral approaches in economics, a new social concept has emerged which is built on human relationships. Being called relational goods, this concept represents the advantages that people derive from their relationships with each other, such as social approval, friendship, companionship, etc. Relational goods that make people feel satisfied and content are generally produced/consumed in positive family and friendship connections. Nowadays it might be expensive to maintain this kind of relations. Spending time on the internet or social media has become more and more appealing for many people. Especially in European countries, where the percentage of people who prefer to be isolated is rising rapidly day by day, the rate of internet use is quite high. This study aims to investigate the impact of the internet on relational goods in Europe based on the data from the 10th Round of the European Social Survey. In this direction, firstly, categorical principal component analysis was employed in order to construct proxy indicators coded as “social relations” and “family relations” instead of relational goods. Afterwards, the relationship between these indicators and internet use was analyzed with the help of figures. The figures suggest that as average daily internet use increases, both social and family relationships weaken. The findings reveal that in countries where people spend less time online, social ties with family, friends, neighbors or close friends are relatively robust; on the contrary, in countries where people use the internet intensively, communication within the family and in social life is generally poor. The results of the regression indicate that in addition to the internet, socio-economic and socio-demographic factors are also determinants of interpersonal relationships. This study, contrary to the literature, finds that in European countries, the use of the internet weakens the ties between people and reduces the production/consumption of relational goods.